Modeling of optical properties of hybrid metal-organic nanostructures - A. N. Ponyavina; K. A. Barbarchyk; A. D. Zamkovets; S. A. Tikhomirov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
To model spectral characteristics of hybrid metal-organic nanostructures, the extended Mie theory was used, which makes it possible to calculate the extinction efficiency factor (Qext) and the scattering efficiency factor in the near zone (QNF) of two-layer spherical particles placed in an absorbing matrix. Two-layer plasmon nanospheres consisting of a metallic core (Ag, Cu) coated with dielectric shells and located into the copper phthalocyanine (CuPc) matrix were considered. The influence of dielectric shell thickness and refractive index on the characteristics of the surface plasmon resonance of absorption (SPRA) was studied. The possibility of the SPRA band tuning by changing the optical and geometrical parameters of dielectric shells was shown. It was established that dielectric shells allow to shift the surface plasmon resonance band of plasmonic  nanoparticles absorption both  to  short-  and  long-wavelength  spectral  range  depending on the relation between shell and matrix refractive indexes.